Estudio De Los Centros Privados Concertados Religiosos, Desde La Perspectiva De Sus Directores Titulares, En El Contexto Multicultural De La Ciudad Autónoma De Ceuta - Arturo Fuentes Cabrera; Arturo Manuel Fuentes Viñas (European Scientific Journal, ESJ, 2016)
World population is constantly changing. That fact offers contexts where the multiculturalism is more important. Ceuta, a Spanish city located in the North of Africa, is one of the best examples of this multiculturalism. In this context, it is interesting to study the development of the education and its staging. In this research, some schools which form the educational offer in the city of Ceuta were taken as models. We were attracted by the idea of carrying out a detailed research about the private and the receiving state subsidy schools which a religious nature, in order to know their features, the connections inside and outside of the centre and the maintenance of them, among other factors. To get that, a quantitative research with surveys has been carried out. At the same time, the semi-structured interviews have provided some qualitative data. In this research, the results show how “difficult” is the survival of these institutions and the preservation of the thinking of all of them in the multicultural context aforementioned. In spite of the complex reality, we conclude by affirming that these institutions are highly regarded in the city of Ceuta.